Conservation Through Eco-Spirituality: A Philosophical Approach to the Residential Patterns and Traditional Architecture of the Kampung Adat Kuta - Nuraeni, Sindi; Agustin, Fitria; Widana, Kendaya; Januar, Hilman; Aditya, Fikri Faisal; Sudarto, Sudarto (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2025)
The study examines the importance of eco-spirituality as a philosophical foundation for the conservation of traditional settlement patterns and architecture in Kampung Adat Kuta. Using a naturalistic qualitative approach, the study draws on literature reviews, in-depth interviews with traditional leaders and local cultural practitioners, and field observations. The findings reveal that the integration of spiritual values and local wisdom embedded in settlement patterns and architectural forms serves as an effective mechanism for environmental and cultural conservation. This study emphasizes that eco-spirituality not only preserves cultural identity but also supports sustainable development in the face of modernization and globalization challenges. The study provides insights into the importance of understanding the philosophical values of natural conservation, the scattered/spreading layout of buildings following norms established by the kuncen (Juru Kunci). In addition to settlement patterns, the topographical conditions and geographical location of the village are intertwined with the philosophical understanding of the Sundanese community. This research is expected to contribute to enhancing understanding and knowledge of the philosophical values of traditional village architecture and natural conservation, inspiring the development of balanced and sustainable life cycles in the future.